Sosialisasi Program Wisata Budaya Di Kelurahan Sei Gohong - Clara, Titha Widya; Romadoni, Muhamad; Jastin, Erik; Ramadhani, Sylvia Putri Malik; Gepeng; Hasan, Putri Julyesti; Anggela, Fridha Maya (Jurnal Pengabdian Kampus, 2024)
One of the tourist settlements that could be converted into a more upscale destination is Sei Gohong. The existence of traditional houses as a part of Palangka Raya City's cultural legacy ought to spur the development of the tourist villages' inventiveness. Sei Gohong Village's problem is the constant, non-increasing number of visitors. Tourists should be drawn in by the presence of built cultural assets close to the tourism sector. Nevertheless, in the process of creating cultural tourism towns, the cultural heritage has not been adequately and creatively utilized as an alternative source. Using lecture and Q&A methods, the community empowerment method was employed in this exercise. Socialization, program sustainability, and evaluation were among the activity stages. In order to socialize cultural tourism, the team worked with the community to conduct a direct field visit as part of their intervention. One of the main draws for travellers visiting Sei Gohong Village is its cultural tourism. Travelers can be drawn in by the use of cultural heritage as a platform for performing arts and technology in regional cultural arts activities. Introducing local culture to visitors as a new tourism attraction may help draw them to the village.